Seasonal variation of inter-limb jumping asymmetries in youth team-sport athletes - Fort-Vanmeerhaeghe, A.; Bishop, C.; Buscà, B.; Vicens-Bordas, J.; Arboix-Alió, J. (Journal of Sports Sciences, 2021)
The main objective of the present study was to provide seasonal variation data for inter-limb asymmetry in youth elite team-sport athletes. Fifty-nine players performed the single-leg countermovement jump (SLCMJ) and the one leg hop for distance (OLHT) tests during pre-season, mid-season and end-season. A repeated-measures analysis of variance was conducted to determine magnitude differences in asymmetry scores between time points. Kappa coefficients (K) were calculated to determine the levels of agreement for the direction of asymmetry. When comparing inter-limb asymmetry magnitudes across the season, the SLCMJ test showed significantly higher asymmetries at mid-season in comparison with pre-season and end-season (p< 0.01, d= -1.03 for pre to mid; p< 0.01, d= 1.12 for pre to end). However, OLHT inter-limb asymmetry magnitude remained consistent throughout the season (ES range = -0.02 to -0.06). For the direction of asymmetry, levels of agreement ranged from poor to slight in the SLCMJ (k= -0.10 to 0.18) and in the OLHT (k= -0.21 to 0.18). No significant differences were found between mean asymmetry values at any time point or for either test when comparing males and females. In conclusion, jump height asymmetry during the SLCMJ was the only metric to show significant magnitude changes across the season.